2019
DOI: 10.3389/fimmu.2019.00898
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection May Trigger Adult-Onset Still's Disease Onset or Relapses

Abstract: Previous studies have revealed that several micro-organisms, especially DNA viruses, have been associated with adult-onset Still's disease (AOSD). However, there are no studies on the relationship between the presence of viral infections in AOSD patients with disease occurrence and reactivation. In the present study, we aimed to investigate the presence of antibodies against virus, virus DNA load and nucleic acid sensors in AOSD patients. Anti-viral antibodies were measured by enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
(35 reference statements)
2
28
0
1
Order By: Relevance
“…[ 4 ]. We now know that cytomegalovirus may also trigger a relapse of AoSD [ 14 ]. Blood cultures and polymerase chain reaction (PCR) tests may, therefore, be useful for a differential diagnosis, although no specific diagnostic algorithms exist to date.…”
Section: Autoinflammation and Autoimmunitymentioning
confidence: 99%
“…[ 4 ]. We now know that cytomegalovirus may also trigger a relapse of AoSD [ 14 ]. Blood cultures and polymerase chain reaction (PCR) tests may, therefore, be useful for a differential diagnosis, although no specific diagnostic algorithms exist to date.…”
Section: Autoinflammation and Autoimmunitymentioning
confidence: 99%
“…Significant associations between AOSD and the HLA DQB1*06:02 allele, as well as between the DRB1*1501-DQB1*06:02 haplotype and AOSD susceptibility have also been observed [10]. Additionally, in recent decades, many cases of an infection with pathogens have been reported in AOSD patients [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MDA5 and anti-CMV IgM is higher in some progressive vitiligo patients Previous study has established that the detective rate of CMV DNA in vitiligo paraffin-embedded vitiligo tissues is up to 38% 14 . To further confirm the link between virus infection and vitiligo, in the serum of progressive vitiligo we first used ELISA to detect anti-CMV IgM, symbolizing acute CMV infection 46 . We found that the positive rate of anti-CMV IgM was 8.92% in 56 progressive vitiligo patients, while that in 26 healthy controls was 3.84%, and the anti-CMV IgM levels were significantly higher in vitiligo patients than that in healthy controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%